Analisis dan Evaluasi Sisa Material Kontruksi Menggunakan FTA (Fault Tree Analysis) Studi Kasus: Proyek Pembangunan Gedung ICU RSUD Limpung Kabupaten Batang - Rahmawati, Diah; Firmawan, Ferry; Auliya, M Bagas; Martiano, Dwiky (Universitas Semarang, 2021)
The rest of the construction material is common occurs in building construction project work, the presence of residual construction materials is unavoidable on construction project work, waste materials construction is also called construction waste can have a negative impact on the environment building construction projects, be it work demolition, renovation, or work related to building construction, research This method uses the Fault Tree Analysis (FTA) method. to analyze the cause of the remaining material occur. As for the type of material being researched, it is brick red, sand, cement, concrete, D16 reinforcing steel, and iron reinforcement 10. The results of the calculation of the cost of the remaining materials red brick Rp. 402,600, sand Rp. 3,137,600, cement Rp. 179.200, concrete Rp. 4,304,325, D16 steel reinforcement Rp. 22,459,110, and reinforcing steel 10 Rp. 3,886,613, from As a result, the largest residual material cost is iron reinforcement D12 and the smallest residual material cost is red brick materials.